2010
DOI: 10.1124/mol.110.065839
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism-Based Inactivation of Cytochrome P450 3A4 by Lapatinib

Abstract: Fatalities stemming from hepatotoxicity associated with the clinical use of lapatinib (Tykerb), an oral dual tyrosine kinase inhibitor (ErbB-1 and ErbB-2) used in the treatment of metastatic breast cancer, have been reported. We investigated the inhibition of CYP3A4 by lapatinib as a possible cause of its idiosyncratic toxicity. Inhibition of CYP3A4 was time-, concentration-, and NADPH-dependent, with k inact ϭ 0.0202 min Ϫ1 and K i ϭ 1.709 M. The partition ratio was approximately 50.9. Addition of GSH did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
139
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(152 citation statements)
references
References 28 publications
12
139
1
Order By: Relevance
“…For the CYP3A4 pathway, time-dependent inhibition was observed for the majority of selected kinase inhibitors, consistent with literature reports where midazolam is used as a probe substrate (Li et al, 2009a(Li et al, ,b, 2010Teng et al, 2010;Kenny et al, 2012). For some of those kinase inhibitors, inactivation mechanisms were also investigated (Teng et al, 2010;Takakusa et al, 2011). As observed for axitinib in our present study, a majority of those compounds have the potential to form reactive intermediates during P450 catalysis, as evident by the formation of glutathione adducts (Kenny et al, 2012).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…For the CYP3A4 pathway, time-dependent inhibition was observed for the majority of selected kinase inhibitors, consistent with literature reports where midazolam is used as a probe substrate (Li et al, 2009a(Li et al, ,b, 2010Teng et al, 2010;Kenny et al, 2012). For some of those kinase inhibitors, inactivation mechanisms were also investigated (Teng et al, 2010;Takakusa et al, 2011). As observed for axitinib in our present study, a majority of those compounds have the potential to form reactive intermediates during P450 catalysis, as evident by the formation of glutathione adducts (Kenny et al, 2012).…”
Section: Discussionsupporting
confidence: 88%
“…Further investigation of this finding is under way to delineate CYP2C8 inactivation mechanisms. For the CYP3A4 pathway, time-dependent inhibition was observed for the majority of selected kinase inhibitors, consistent with literature reports where midazolam is used as a probe substrate (Li et al, 2009a(Li et al, ,b, 2010Teng et al, 2010;Kenny et al, 2012). For some of those kinase inhibitors, inactivation mechanisms were also investigated (Teng et al, 2010;Takakusa et al, 2011).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…An in vitro investigation showed that lapatinib was metabolized to O-dealkylated lapatinib by CYP3A4 and CYP2C8, and GSH and cysteinyl-glycine conjugates were also observed (Teng et al, 2010). Although allitinib was metabolized by O-dealkylation, like lapatinib, we detected no conjugates formed by the reaction between GSH and the quinone imine intermediate.…”
Section: Metabolism Of Allitinib In Humans 881mentioning
confidence: 60%